Joint Modelling of Power Price, Temperature, and Hydrological Balance with a View towards Scenario Analysis - Veronika Lunina (Lund University, School of Economics and Management, Department of Economics, 2016)
This study presents a model for the joint dynamics of power price, temperature, and hydrological balance, with a view towards scenario analysis. Temperature is a major demand-side factor affecting power prices, while hydrobalance is a major supply-side factor in power markets dominated by hydrological generation, such as the Nordic market. Our time series modelling approach coupled with the skew-Student distribution allows for interrelations in both mean and volatility, and accommodates most of the discovered empirical features, such as periodic patterns and long memory. We find that in the Nordic market, the relationship between temperature and power price is driven by the demand for heating, while the cooling effect during summer months does not exist. Hydrobalance, on the other hand, negatively affects power prices throughout the year. We demonstrate how the proposed model can be used to generate a variety of joint temperature/hydrobalance scenarios and analyse the implications for power price.
Keywords: C32; G17; Q41; 330; spot power price; temperature; hydrological scenarios; VARFIMA-BEKK; skew-Student